The New Political Economy of Land Reform in South Africa
XI, 282 p. 4 illus., 3 illus. in color.
Keywords: This book analyzes the new political economy of land reform in South Africa. It takes a holistic approach to understand South Africa’s land reform, assesses the current policy gaps, and suggests ways of filling them. Due to its cross-disciplinary approach, the book will appeal to a broad audience, and will benefit readers from the fields of policy reform, administration, law, political science, political economics, agricultural economics, global politics, resource studies and development studies. Adeoye O. Akinola is Post-Doctoral Fellow, Department of Public of Administration, University of Zululand, South Africa. Irrshad Kaseeram is Professor and Dean at the Department of Administration and Law, University of Zululand, South Africa. Nokukhanya N. Jili is Head of the Department of Public Administration, University of Zululand, South Africa.